The Impact of Hospital Image on Patient Loyalty: A Study on Private Islamic Hospitals in Mataram City West Nusa Tenggara - Muin, Abdul; Menap, Menap; Setiawan, Sabar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study employed an observational analytic design with a cross-sectional approach to examine the impact of hospital brand image on patient loyalty in private Islamic hospitals in Mataram. Data were collected from 223 patients at RSI Siti Hajar Mataram using structured questionnaires. The sample was selected through proportional stratified random sampling, ensuring representation across various hospital care classes.The findings of this study reveal that: (1) a positive hospital brand image significantly correlates with patient loyalty (p ≤ 0.001); (2) 96.5% of patients with a positive perception of the hospital’s image demonstrated high loyalty; (3) demographic factors, such as age, gender, and education level, influence patients’ perceptions of the hospital brand image; and (4) Muslim patients exhibited higher loyalty levels compared to non-Muslim patients, highlighting the relevance of Islamic values in healthcare services.The study underscores the critical importance of developing a positive brand image to enhance patient loyalty. Hospitals should adopt comprehensive strategies to improve service quality, ensure effective communication, and align their services with patients’ cultural and religious values. These efforts can foster trust, strengthen the hospital’s reputation, and secure long-term patient retention, particularly in culturally sensitive contexts.